TRASER - Total Reflection Amplification of Spontaneous Emission of Radiation - Zachary, Christopher B.; Gustavsson, Morgan (PLOS ONE, 2012)
Background and Objective Light and lasers in medical therapy have made dramatic strides since their invention five decades ago. However, the manufacture of lasers can be complex and expensive which often makes treatments limited and costly. Further, no single laser will provide the correct parameters to treat all things. Hence, laser specialists often need multiple devices to practice their specialty. A new concept is described herein that has the potential to replace many lasers and light sources with a single ‘tunable’ device. Study Design/Material and Methods This device amplifies spontaneous emission of radiation by capturing and retaining photons through total internal reflection, hence the acronym Total Reflection Amplification of Spontaneous Emission of Radiation, or TRASER. Results Specific peaks of light can be produced in a reproducible manner with high peak powers of variable pulse durations, a large spot size, and high repetition rate. Conclusion Considering the characteristics and parameters of Traser technology, it is possible that this one device would likely be able to replace the pulsed dye laser and many other light based systems.